Treehouse Trouble: Muk'n' Honey # 1 - Bean, Brett (New York : Penguin Workshop, 2025)
As forest inventors Honey Bunny and Muk Muk help their friends resolve their problems, they inadvertently find a solution to their own stubborn dilemma.
Ages 6-9.
Keywords: Inventions -- Fiction; Problem solving -- Fiction; Animals -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Animal fiction